Raban Maur, Homilie o najważniejszych świętach oraz o cnotach (wybór) (Homiliae de festis praecipuis, item de virtutibus) - Gacia, Tadeusz; Adamiak, Jarosław; Strycharczuk, Agnieszka; Turkiewicz, Natalia (Vox Patrum, 2016)
nie dotyczy